Hubungan Kemampuan Baca dengan Prestasi Akademik Siswa - Lusi Romaddyniah Sujana; Andri Yanto; Prijana Prijana (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2017)
This research was conducted in order to readability using good reading method with student academic achievement and readability using reading habit method with student academic achievement. The method used in this study is quantitative using experimental studies. The population of this study is all students of class VIII in SMPN 1 Cileunyi Kab. Bandung. The sample of this study was the experimental group reading the 500 word text (N = 41), the control group reading the 500 word text (N = 41), the experimental group reading the text of 1,000 words (N = 43), the control group reading the text of 1,000 words (N = 40), after reading the text given the test to answer the question multiplechoice. The results of this study indicate that the readability using the good reading method and reading habit methods has a significant relationship with academic achievement. There is a significant distinction between reading ability of the text using the method of read reading habit (1,000 words) by the method of reading good reading (1,000 words).